Polyostotic fibrous dysplasia: imaging findings of a controversial case - Francesca De Michele; Francesca A. Carpagnano; Maria T. Paparella; Giuseppe Guglielmi (Digital Diagnostics, 2022)
Fibrous dysplasia is a rare non-neoplastic tumor-like congenital bone disease that is most likely associated with GNAS gene mutations, with a broad spectrum of clinical presentations, ranging from isolated monostotic and polyostotic forms to other extra-skeletal associated manifestations as in McCuneAlbright syndrome. It is responsible for bones weakening and increased fragility, making it prone to fractures.